Transcending Capitalism : Visions of a New Society in Modern American Thought - Brick, Howard, 1953- (Book collections on Project MUSE., 2006)
"Transcending Capitalism: Visions of a New Society in Modern American Thought explains why many influential midcentury American social theorists came to believe it was no longer meaningful to describe modern Western society as "capitalist," but instead preferred alternative terms such as "postcapitalist," "postindustrial," or "technological." Considering the discussion today of capitalism and its global triumph, it is important to understand why a prior generation of social theorists imagined the future of advanced societies not in a fixed capitalist form but in some course of development leading beyond capitalism."--Jacket.